Paddy Price Prediction using Fuzzy Time Series Model Lee Method for Determination of Crop Insurance Premiums - Hidayat, Agus Sofian Eka; Amanifalah, Deati; Primajati, Gilang (Balai Publikasi Indonesia, 2024)
The price of the paddy has significant fluctuations as BPS mentioned that the average price of dry paddy harvested at the farmer level decreased in February 2022 by 3.2% from January 2022. Hence, crop industry businesses continue to face significant uncertainty risk. The purpose of this study is to discuss the use of the Fuzzy Time Series Model Lee for predicting future paddy prices in order to calculate crop insurance premium using Black Scholes model with cash or nothing put option approach. This is because crop industry is one of the agricultural products that Indonesia is capable of producing in large quantities. As a result, crop insurance should be purchased by farmers to protect against crop yield losses. Aside from that, the price of paddy fluctuates significantly. Therefore to reduce the loss of revenue from reductions in decreasing of crop yield or even crop failure, it needs to provide the insurance based on the paddy prices to protect the paddy prices itself from the large fluctuations at the farmer level. Based on the analysis of this study, generates result for January 2022, February 2022, and March 2022 are 4547.41, 4547.41, and 4701.62 respectively. With the accuracy level is 0.05%. Therefore, the insurance premiums based on the prediction result is 2,775,579. The implication or benefit of this thesis is for the other parties such as farmer